What Spanish can tell us about the syntax of eventives vs. stative verbal predicates - McDonald, Jonathan E. (Borealis – An International Journal of Hispanic Linguistics, 2024)
The main goal of this article is to argue and provide support for the distinction between eventive and stative verbal predicates being encoded in the syntax. More specifically, following Travis (1991, 2010, MacDonald 2008, Kardos & Farkas 2022), I provide arguments for the existence of an aspectual functional projection situated between Voice and VP: AspP. I argue that eventive verbal predicates project AspP and stative verbal predicates do not. Its syntactic presence serves as input to semantics giving rise to a dynamic predicate, a predicate that entails (some amount of) change along a scale, based on scalar approaches to eventive verbal predicates (Hay et al. 1999, Kennedy & Levin 2008, Beavers 2011, 2013, among others). Empirically, I discuss two phenomena from Spanish: hacerlo "do so" substitution and verbal interfixes, like ot in fregotear "to scrub at" (vs. fregar "to scrub"). I argue that hacer selects for AspP while the verbal interfixes head Asp. Support for the main proposal that there is a syntactic distinction between eventives and statives emerges from the ungrammaticality of hacerlo when it takes a stative verbal antecedent and the fact that the output of interfixation does not give rise to stative verbal predicates, only eventive verbal predicates